STRATEGIC DEVELOPMENT OF PRICING, BRAND EQUITY, AND PRODUCT QUALITY IN DRIVING CONSUMER PURCHASE DECISIONS: EMPIRICS FROM VIRGIN COCONUT OIL MSMES IN NORTH MINAHASA, INDONESIA - Silvya Lefina Mandey; Victor Paskah Kalawat Lengkong; Jenny Emma Agustin Kandou (Management Studies and Business Journal (PRODUCTIVITY), 2025)
Virgin Coconut Oil (VCO) is increasingly valued for its nutritional and therapeutic properties, offering a strategic opportunity for micro, small, and medium enterprises (MSMEs) in North Sulawesi, Indonesia. Yet, limited standardization, weak branding, and inconsistent pricing hinder competitiveness. This study analyzes how pricing strategy, brand equity, and product quality individually and jointly influence consumer purchase decisions for VCO products in North Minahasa Regency. Using a quantitative, associative-causal design, data were collected from 100 consumers selected through purposive sampling. Multiple linear regression reveals that product quality exerts a positive and significant influence on purchase decisions (p < 0.05), whereas pricing strategy and brand equity show no significant individual effects. Nevertheless, all three variables together significantly affect purchase behavior (F = 6.166, p = 0.001), explaining 16.2 percent of total variance. The findings underscore that consumers prioritize functional attributes; purity, clarity, and durability over price or brand cues. Policy-wise, the study recommends value-based pricing, consistent quality control, and long-term brand building to strengthen MSME competitiveness in Indonesia’s coconut industry.